Malaysia Economic Monitor - Catching Up : Inclusive Recovery Growth for Lagging States - World Bank (Washington, DC: World Bank, 2022)
Global growth slowed markedly in H1 2022. This was due to COVID-19 resurgences at the turn of the year; protracted supply disruptions; reduced macroeconomic support; and substantial negative spillovers from the war in Ukraine. The conflict, which has sparked the largest commodity price shock in 50 years, has exacerbated the increasingly difficult policy tradeoffs between supporting growth and managing price pressures. It has contributed to tightening in global financial conditions, increased financial market volatility and higher borrowing costs, particularly in Emerging Markets and Developing Economies (EMDEs).